Gender, elderly and health care - Barrantes Monge, Melba (Acta Bioethica, 2006)
It is necessary to consider the bioethical principles of beneficence and justice for giving individual health care to elderly women and for generating a health care system (or public policies) with an ethical approach where equity will be always present. In order to be fair and beneficent one must be efficient, which is achieved considering particular factors of the elderly: physical and mental health, quality of life, their real access to the health care services among others.